The quota system for acess to the labor market for people with disabilities: a qualitative analysis based on the fundamental rigth to The existential maximum (Research, Society and Development, 2022)
The most relevant aspects of this study fall on the quota system (Law nº 8.112/90 and Law nº 8.213/91) and the analysis of access to the labor market by people with disabilities (PCD), substantiating the qualitative aspect in Law nº 13.146/2015. In this context, the research question is limited to questioning whether the foundation of the application of the fundamental right to the existential maximum is present in work relationships directed to PCD through the Quota System? The objective is to analyze from a qualitative point of view the quota system aimed at PCD in the labor market, using relevant aspects of the fundamental right to the existential maximum for the direction and strategies of inclusion, based on different approaches to equality as a process of respect. the difference. The research has a descriptive nature, which deals with phenomena that are little known or that are not yet very clear, due to their degree of complexity, fragmentation and interconnections, based on the qualitative method, according to which data analysis is an effective instrument to expand knowledge about the researched subject. Data were collected in literary bases of broad and diversified works, as well as in legislation, official government websites and online events. Thus, the main results obtained reverberated in verifying that the group object of study needs special attention, due to their vulnerabilities, concerning the restriction of locomotion, vision, hearing, among others, seeking to implement the right to equality and the fundamental right to the maximum existential within working conditions, considering that these rights will attract, by way of accessory, the duty of solidarity, accessibility, social justice, in order to guarantee a dignified life for the disabled person and in order to avoid the state of objectification of the human being.